Effect of Age and Lipoperoxidation in Rat and Human Adipose Tissue-Derived Stem Cells. (9th December 2020) - Muñoz, Mario F.; Argüelles, Sandro; Marotta, Francesco; Barbagallo, Mario; Cano, Mercedes; Ayala, Antonio
Abstract : A wide range of clinical applications in regenerative medicine were opened decades ago with the discovery of adult stem cells. Highly promising adult stem cells are mesenchymal stem/stromal cells derived from adipose tissue (ADSCs), primarily because of their abundance and accessibility. These cells have multipotent properties and have been used extensively to carry out autologous transplants. However, the biology of these cells is not entirely understood. Among other factors, the regeneration capacity of these cells will depend on both their capacity of proliferation/differentiation and the robustness of the biochemical pathways that allow them to survive under adverse conditions like those found in damaged tissues. The transcription factors, such as Nanog and Sox2, have been described as playing an important role in stem cell proliferation and differentiation. Also, the so-called longevity pathways, in which AMPK and SIRT1 proteins play a crucial role, are essential for cell homeostasis under stressful situations. These pathways act by inhibiting the translation through downregulation of elongation factor-2 (eEF2). In order to deepen knowledge of mesenchymal stem cell biology and which factors are determinant in the final therapeutic output, we evaluate in the present study the levels of all of these proteins in the ADSCs from humans and rats and how these levels are affected by aging and the oxidative environment. Due to the effect of aging and oxidative stress, our results suggest that before performing a cell therapy with ADSCs, several aspects reported in this study such as oxidative stress status and proliferation and differentiation capacity should be assessed on these cells. This would allow us to know the robustness of the transplanted cells and to predict the therapeutic result, especially in elder patients, where probably ADSCs do not carry out their biological functions in an optimal way.